Gaps in availability, utilization and expectations of people from health care services: A study of resettlement colony, Chandigarh - Gandhi, Mamta; Narang, Kavita; Kaur, Manmeet (Indian Journal of Community Health, 2014)
Introduction: Health care services cover a wide spectrum of community services for the treatment of disease, prevention of illness and promotion of health.[1] Aim and Objective: This study was aimed at assessing the gap in availability and utilization of health services in a resettlement Colony of Chandigarh. Material and methods: Dadu Majra was purposely selected to assess the gap in availability and utilization of health care services and expectations of people from public health sector. Using semi structured interview schedule, interviews were carried with all health care providers. Six focused group discussions and interviews were held 114 sampled service users. Results: Most of the users were utilizing services from private medical clinics (96.5%) for the treatment of acute illnesses. For antenatal checkup/delivery (95.6%), chronic diseases (99.1%), and emergency services (95.6%) Government Multi-Speciality Hospital, Chandigarh was being utilized. Utilization of services provided at civil dispensary of study area was low. The expectations of users were availability of at least one doctor and availability of free medicine & laboratory facilities. Conclusions: Public health services were preferred over by the private and therefore need to be strengthened.